Nutritional Evaluation of Gum Arabic and Its Food Products Locally Prepared in Tharparkar, Sindh, Pakistan - Pawan Kumar; Aijaz Hussain Soomro; Asadullah Marri; Omer Mukhtar Tarar; Nida Shaikh; Asif Irshad; Allah Bux Baloch; Muhammad Dawood (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Gum Arabic is an edible, dried, gummy exudate extracted from the stems and branches of Acacia Senegal. It is commonly used in the pharmaceutical and food industries as an emulsifier and stabilizer agent. The present study assessed the nutritional composition of gum Arabic (T1) and its food products, namely T2 (Khorak) and T3 (Gond Pak), which were locally prepared in Tharparkar, Sindh, Pakistan. Gum Arabic was sourced from the local tree Acacia Senegal, whereas its food products, i.e., Khorak and Gond Pak, were prepared and evaluated for proximate composition, amino acids profiling, minerals, and vitamins quantification. The observed results showed significant differences (p ≤ 0.05) among treatments. The T1 exhibited higher values for ash (3.17%), dietary fiber (66.10%), titratable acidity (1.5%), valine (0.30 mg/g), serine (0.68 mg/g), potassium (254.22 mg/100g), sodium (118.55 mg/100g), calcium (7976.30 mg/kg), magnesium (2061.5 mg/kg), iron (76.57 mg/kg), and thiamine (7.74 mg/100g). T2 showed higher pH (5.47), moisture (11.61%), carbohydrate (39.25%), energy value (308.65 kcal/100g), methionine (0.02 mg/g), isoleucine (0.16 mg/g), leucine (0.68 mg/g), tyrosine (0.39 mg/g), lysine (3.35 mg/g), vitamin A (141.33 IU/100g), vitamin C (4.65 mg/100g), niacin (26.25 mg/100g), and pyridoxine (0.06 mg/100g). T3 had higher protein (12.29%), crude fat (15.99%), aspartic acid (1.66 mg/g), threonine (0.533 mg/g), glutamic acid (4.43 mg/g), proline (0.079 mg/g), glycine (0.446 mg/g), alanine (0.443 mg/g), phenylalanine (0.54 mg/g), histidine (0.20 mg/g), tryptophan (0.92 mg/g), riboflavin (0.71 mg/100g), folate (21.97 mg/100g), and cyanocobalamin (1.17 mg/100g). Cysteine, arginine, vitamin D, E, pantothenic acid, and biotin were not detected in any treatments. The study concludes that gum Arabic and its food products are highly nutritious, suggesting their suitability for consumption in regions with prevalent malnutrition.